Review on camel production and marketing status in Ethiopia - Doyo Kena (Pastoralism, 2022)
Abstract Pastoralism has been the most productive livelihood option in the dryland of the Horn of Africa although recently its sustainability is becoming challenging. Camel is a livestock species uniquely adapted to the arid and semi-arid areas of the region. Camels are predominantly reared in the drier areas of Ethiopia such as Afar, Ethiopian Somali and the eastern and southern parts of Oromia region. This review is aimed at reviewing the camel population, marketing status, challenges and opportunities related to camel production and marketing in Ethiopia. Official reports on the camel population (1.42 million) underestimate the number of camel populations in Ethiopia while different research reports a higher figure of the camel population up to 4.8 million. However, each report indicated an increasing trend in the camel population. Camel is being adopted by different pastoral groups, in which camel rearing was less customary. The economic importance of the camel over other livestock species is immense, particularly during the harsh seasons due to less decline in its prices and the camel is the most expensive in both pastoral and agro-pastoral areas when compared to other livestock. Camel plays an important role in revenue generation, contributing to the earnings from export. Formal camel export status has shown a flat trend and informal export outweighed the formal one. Despite its ecological and economic importance, the camel has been neglected by researchers and the Ethiopian government. Poor market infrastructure, lack of market information, lack of market-oriented production system, the export ban by many countries and the inconvenience of an export regulatory institutional setting are among the major constraints of camel marketing in Ethiopia. Therefore, policy and development interventions are demanded that recognize the social, economic and ecological importance of camels for pastoral communities and the national economy.